Sistem Informasi Simpan Pinjam Koperasi Citra Abadi - Yuan Pratama; Lily Puspa Dewi; Alexander Setiawan (Jurnal Infra, 2021)
Currently, the Citra Abadi savings and loan cooperative is still running all of its business processes manually. Cooperative recording is still done manually by means of books and paper. As a result of the system that is still manual, cooperative employees often find it difficult to find the required data quickly, for example when looking for member data, savings and loan data. Cooperative employees must find this data from the pile of cooperative records. It is also less effective and there is often missing data. Problems are also found when calculating reports in the cooperative, such as SHU reports, savings reports, and loan reports, the calculation process will take a very long time because you have to manually collect data which will be calculated one by one manually using a calculator. HTML 5 web-based information systems and PHP is built using Bootstrap framework and MySQL database. Features provided include: members data, saving and loan, remaining business results, promotion, balance, and survey data. The results obtained from the creation of this information system are that users can find out member data along with savings and loans, survey data, and receive reports needed by cooperative managers. From the results of the questionnaire, there are 100% on the assessment of good savings and loan features, 100% on the assessment of good application speed, and 66.7% on the overall assessment of the application is good.